Robust synthesis of enantiopure cyclohexenyl analogues of 2/3-deoxyribose sugars as carbocyclic nucleoside precursors - Varada, Manojkumar; Kotikam, Venubabu; Kumar, Vaijayanti A. (Tetrahedron, 2011)
An expedient synthesis of 2-deoxy (10) and 3-deoxy (11) cyclohexenyl analogues of 2-deoxy and 3-deoxy-D-ribose sugar from commercially available starting materials is reported. Highly efficient enzymatic resolution of the key compound 10 is described using lipase under hydrolytic conditions. The robust methodology applied here will be useful to synthesize cyclohexenyl nucleosides, which possess potent antiviral activity and are capable of gene silencing via RNAi or antisense applications. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Carbocyclic mimics of 2-deoxy-D-ribose and 3-deoxy-D-ribose Enzymatic resolution; CeNA; DA reaction

Comparing the interactions of DNA, polyamide (PNA) and polycarbamate nucleic acid (PCNA) oligomers with graphene oxide (GO) - Kotikam, Venubabu; Fernandes, Moneesha; Kumar, Vaijayanti Anil (Physical Chemistry Chemical Physics, 2012)
The fluorescently labelled short octameric oligothymine sequences of DNA, PNA and PCNA were used in fluorescence quenching studies in conjunction with dispersed graphene oxide. The measurable restoration of their fluorescence by complementary oligodeoxyadenylate was compared. This is the first study aimed at replacing the natural DNA probes with synthetic DNA mimics that show excellent properties in terms of formation of very strong duplexes with cDNA in addition to their stability towards proteases and nucleases.

Synthesis and properties of 2 `-O-[R- and S-(2-amino-3-methoxy)propyl] (R-AMP and S-AMP) nucleic acids - Kotikam, Venubabu; Kumar, Vaijayanti A. (Tetrahedron, 2013)
Substitution at 2'-position by either amino- or methoxy-pendant groups of the antisense oligonucleotides (AONs) is known to enhance their therapeutic value. A simple modification is described here in which we introduce both these groups in the form of enantiospecific tethers at 2'-position. Practical synthesis of modified nucleosides using natural L-serine, en route to R-AMP- and S-AMP-AONs is presented. Such tethered ONs formed stable DNA:RNA duplexes and the stability was found to be marginally better than the methoxyethyl/methoxypropyl-substituted MOE/MOP-AONs. The stereochemistry of the tether effectively differentiated the hydrolytic cleavage of AONs and the R-AMP-AON was three times more stable than the S-AMP-AONs after 4 h. In comparison, the MOE- or MOP-AONs were almost completely digested by SVPD after 1 h. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Antisense therapeutics; MOE-AONs; Positively charged ON analogues

Inhibition of miR-21 by 3 `/5 `-serinyl-capped 2 `-O-Methyl RNA Interspersed with 2 `-O-(2-Amino-3-Methoxypropyl) uridine units - Nahar, Smita; Kotikam, Venubabu; Kumar, Vaijayanti A.; Maiti, Souvik (Nucleic Acid Therapeutics, 2016)
miRNAs are highly conserved class of small ncRNAs whose involvement in human pathophysiologies is extensively investigated. MiR-21 is a well established oncogenic miRNA whose deregulation plays a significant role in onset and progression of cancer. The need of novel approaches to downregulate miR-21 is rapidly expanding. Potent inhibition of miR-21 is achieved by chemically modified 2-O-methyl RNA oligonucleotide. The serinol capping at 3 and 5ends and the interspersed 2-O-(R-2-amino-3-methoxypropyl) uridine units enhance the nuclease resistance and efficacy of 2-O-methyl RNA for the inhibition of miR-21. This represents a simple and novel modification for developing oligonucleotide-based therapeutics.
Keywords: antagomirs; cancer; microRNA; noncoding RNA; oligonucleotides